The Inner Structure of STEVE‐Linked SAID. Issue 8 (25th April 2023) - Mishin, Evgeny V.; Streltsov, Anatoly V.
Abstract: We found the inner electromagnetic structure of subauroral ion drifts (SAID) in the SAID‐STEVE events documented by the Swarm spacecraft and numerically simulated the ionospheric feedback instability (IFI) development for one of the four similar events. Good quantitative agreement of the modeling results with the observed features shows that the ionospheric feedback mechanism captures their basic underlying physics. Simulations require nonlinear saturation of the IFI‐generated dispersive Alfvén waves. That is, a strong driving field of STEVE‐linked SAID with a deep density trough leads to a nonlinear system of dispersive Alfvén waves coupled with the density perturbation and parallel electric fields. As shown earlier, these fields produce the suprathermal electron population and energy balance necessary for the STEVE and Picket Fence radiation. Therefore, our results predict their inner structure. Plain Language Summary: Interpretation of subauroral arcs—STEVE and Picket Fence—inside fast subauroral flows (SAID) with depleted density and high electron temperature requires specific local distributions of ionospheric electrons and vibrationally excited neutrals. It was earlier shown that the ionospheric feedback instability in STEVE‐linked SAID could provide the required features. The resulted meridional structure was not explored further, though it is essential for validation of the feedback mechanism. We discovered the inner electromagnetic structure of four similar, well‐documented SAID‐STEVE events from the Swarm spacecraft and numerically simulated the IFI development for one of these. Good quantitative agreement between the simulated and observed structures shows that the ionospheric feedback mechanism captures the basic underlying physics. Therefore, our results predict the inner structure of STEVE and Picket Fence. Key Points: Swarm satellite observations reveal the inner electromagnetic structure of STEVE‐linked subauroral ion drifts (SAID) Ionospheric feedback instability (IFI) simulation reproduces the observed structure The generated nonlinear Alfvénic system coupled with the parallel electric fields makes the inner structure of STEVE and Picket Fence